PENGGUNAAN METODE FORWARD CHAINING DALAM PERANCANGAN SISTEM PAKAR DIAGNOSA GANGGUAN KEJIWAAN - Fransiskus Panca Juniawan (UNIVERSITAS INDO GLOBAL MANDIRI)
Healthy life is not only oriented to physical health in the human body, but mental health is also important to keep the soul is not disturbed. Many people have psychiatric disorders, but they ignore it, so his mental health becomes a nuisance. People who have mental disorders also have difficulty for treatment. They must find the experts who are experts in mental disorder, and seek solutions to his recovery. It all costs a lot. Along with the advance of development technology, it can be made an application to help us to diagnose psychiatric disorders in humans so that patients with psychiatric disorders can make the initial diagnosis without having to come to the experts. This research is doing psychological system design. This study consists of data analysis conducted by collecting data obtained from psychology books or related to medical science related to psychology. Then from the data obtained successfully then translated into a graph of knowledge, decision tables, and decision trees. The use of forward chaining method in designing the development of the premise, namely reasoning first, and then testing the truth of the hypothesis. The result of this research is the design of expert system of psychological disorder diagnosis which in the next research can be developed into the final application that can be applied and used by the public.Keywords : Expert System, Psychiatric Disorder, Forward Chaining, Designing